2016
DOI: 10.1111/ctr.12819
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular events in 20 years of follow‐up after liver transplantation: an underestimated issue?

Abstract: LT recipients seem to have a considerably increased risk of CBVE. Long-term surveillance should take this into account, and screening may be extended accordingly. The progressive impairment of renal function in the long-term LT survivors may be one reason for the underestimation of CBVE in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several aspects of cerebrovascular diseases in LT recipients have been investigated, including prevalence and related risk factors [22][23][24].…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several aspects of cerebrovascular diseases in LT recipients have been investigated, including prevalence and related risk factors [22][23][24].…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%
“…To test whether LT might have an effect on the incidence of cerebrovascular events, i.e., stroke or transient ischemic attack (TIA), a retrospective cohort of 313 LT recipients were studied according to their PROCAM Stroke scores and their 20-year follow-up [24]. In this study population, the risk of cerebrovascular events in LT recipients was 3.5-fold higher that it was during the first 10 years and 2-fold higher in the second decade after LT than it was in "the standard population" (Table 2).…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%
“…Increasing age of the recipients and high incidence of cardiovascular risk factors, but also calcineurin inhibitor treatment, are positive predictors. Schoening et al showed that the risk of cerebrovascular events was around 3.5 times higher in the first decade after LT and 2 times higher in the second decade after LT compared with the standard population 55…”
Section: Non-rhe Pltementioning
confidence: 99%
“…Solid organ transplantation has become the definitive and life‐saving treatment for patients with end organ disease. Although graft complications and infections are still the main causes of mortality, long‐term outcomes after transplantation can be substantially influenced by other postoperative complications related to thromboembolism and cardiovascular events .…”
Section: Introductionmentioning
confidence: 99%